Non-Parasitic Chyluria: A Rare Experience (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Chyluria is the passage of chyle in the urine. The cause seems to be the rupture of retroperitoneal lymphatics into the pyelocaliceal system, giving urine a milky appearance. This condition if left untreated leads to significant morbidity because of hematochyluria, recurrent renal colic, nutritional problems due to protein losses and immunosuppression resulting from lymphocyturia.Chatt Maa Shi Hosp Med Coll J; Vol.19 (2); July 2020; Page 59-62